THE ROLE OF PERCEIVED VALUE IN MEDIATING THE EFFECT OF PACKAGING DESIGN AND BRAND IMAGE ON PURCHASE INTENTION OF PENTOLAN - Nicholas Alexander; Michael Ricky Sondak (RADJA PUBLIKA, 2026)
The transformation of the culinary industry requires MSMEs, particularly in the street food sector, to adapt visually and strategically to modern consumer behaviour. This study aims to analyse the role of perceived value in mediating the effect of packaging design and brand image on the purchase intention of